OPTIMALISASI TEKNOLOGI INFORMASI UNTUK PENINGKATAN KUALITAS PEMBELAJARAN - A. Aviv Mahmudi (Jurnal Pengabdian Vokasi, 2021)
Madrasah Aliyah Mu'allimin Mu'allimat Rembang (M3R) during the Covid-19 M3R pandemic held distance education using online methods. However, the problem of online learning models cannot be done optimally because of the lack of ability of teachers in creating learning content / materials. Teachers also do not have the ability to make video-based material to support the learning process. Through this activity, it is hoped that it can improve the quality of learning and education. So that by providing community service programs through these trainings, teachers are able to improve their abilities as professional teaching staff who understand the importance of ICT in learning activity.